Etika Pemanfaatan Artificial Intelligence dalam Pembelajaran Adaptif di Sekolah Dasar: Perspektif Guru dan Siswa di Kabupaten Rejang Lebong - Raudya Tuzzahra (Digital Pedagogy in Primary Education Journal, 2026)
The integration of Artificial Intelligence (AI) into adaptive learning offers personalized education but raises complex ethical dilemmas at the elementary school level. This mixed-methods study explored the ethics of AI use in adaptive learning in elementary schools in Rejang Lebong Regency from the perspectives of teachers and students. Quantitative data were collected through surveys of 100 teachers and 200 students in grades IV, V, and VI, while qualitative data were obtained through interviews with 55 key informants comprising 25 teachers and 30 students. The findings revealed polarization in educators’ ethical awareness, categorized as high (8 teachers), moderate (9 teachers), and low (8 teachers). Teachers with high ethical awareness were critical of children’s data privacy protection, whereas those with low awareness tended to rely excessively on automated assessment for administrative convenience. Students reported psychological anxiety and digital alienation arising from rigid algorithmic interactions and automatic labeling, which were exacerbated by limited local network infrastructure. The study recommends formal regulations and ethical guidelines for AI use by the local Department of Education to ensure pedagogical fairness and protect children’s personal data.   Keywords: adaptive learning; Artificial Intelligence; elementary school; ethics of technology; teacher and student perspectives